Modeling the number of university graduates for the development of the economy of the Kemerovo region - T. V. Bobko; T. I. Efremkova; T. V. Petrova (Вестник университета, 2024)
In the conditions of innovative economy development, the formation issues of the personnel and research potential of the region at the expense of local universities’ graduates are of particular importance. The article puts forward and confirms the hypothesis that a number of socio-economic development indicators of Kemerovo region significantly affect the number of graduates of regional universities, which can be predicted considering changes in these indicators. With the help of the created model, it is possible to study the impact of each of the arguments of the model on the number of university graduates, predict their dynamics, identify targets for the management decisions development in the field of regulating the number of young specialists with higher education (necessary for the regional economy), as well as formulate strategic planning tasks and assess university development the potential. The results of the study can be used by structural divisions of the Government of Kuzbass, the leadership of universities and organizations of the Kemerovo region.